2021
DOI: 10.1242/jeb.242168
|View full text |Cite
|
Sign up to set email alerts
|

Limited heat tolerance in a cold-adapted seabird: implications of a warming Arctic

Abstract: The Arctic is warming at approximately twice the global rate, with well-documented indirect effects on wildlife. However, few studies have examined the direct effects of warming temperatures on Arctic wildlife, leaving the importance of heat stress unclear. Here, we assessed the direct effects of increasing air temperatures on the physiology of thick-billed murres (Uria lomvia), an Arctic seabird with reported mortalities due to heat stress while nesting on sun-exposed cliffs. We used flow-through respirometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 74 publications
4
20
0
Order By: Relevance
“…High-latitude seabird species may be particularly vulnerable to the direct effects of global warming, as they are adapted to conserve rather than lose heat and therefore show limited heat tolerance (Choy et al 2021). One such high-latitude species is the common guillemot Uria aalge.…”
Section: Introductionmentioning
confidence: 99%
“…High-latitude seabird species may be particularly vulnerable to the direct effects of global warming, as they are adapted to conserve rather than lose heat and therefore show limited heat tolerance (Choy et al 2021). One such high-latitude species is the common guillemot Uria aalge.…”
Section: Introductionmentioning
confidence: 99%
“…Many Arctic animals are cold specialists and have evolved physiological adaptations for minimizing heat loss [24,25]. Consequently, high-latitude breeding species are probably vulnerable to even moderate increases in ambient temperature [26][27][28][29]; an alarming fact given that the Arctic has warmed faster than the global average and is expected to continue outpacing the global average over the twenty-first century [4]. Additionally, O'Connor et al [26] recently showed that buntings become heat-stressed at moderate air temperatures and have an extremely limited evaporative cooling capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Our prediction was that higher THg levels would result in greater movements due to reductions in PRL that may negatively impact incubation consistency (Tartu et al 2015(Tartu et al , 2016. However, in our study, the combination of THg and heat stressors resulted in less incubation interruptions, potentially due a more complex system than anticipated that includes the reaction of females to acute heat stress, as well as the supressing effect of THg on CORT, which in-turn may interact with PRL levels (Provencher et al 2016;Tartu et al 2015;Choy et al 2021). Females with lower THg levels may have a heightened acute stress response to heat exposure outside of their thermal limits, releasing CORT that supresses PRL and results in greater incubation interruptions (Tartu et al 2015;Choy et al 2021).…”
Section: Impact Of Multiple Stressor Exposure On Incubation Interrupt...mentioning
confidence: 58%
“…However, in our study, the combination of THg and heat stressors resulted in less incubation interruptions, potentially due a more complex system than anticipated that includes the reaction of females to acute heat stress, as well as the supressing effect of THg on CORT, which in-turn may interact with PRL levels (Provencher et al 2016;Tartu et al 2015;Choy et al 2021). Females with lower THg levels may have a heightened acute stress response to heat exposure outside of their thermal limits, releasing CORT that supresses PRL and results in greater incubation interruptions (Tartu et al 2015;Choy et al 2021). While this action is a potential self-preservation method to obtain water and prevent dehydration, the female risks egg overheating and greater predation risk due to female absence and movements attracting predators (Smith et al 2012;Geldart 2021;Ridley et al 2021).…”
Section: Impact Of Multiple Stressor Exposure On Incubation Interrupt...mentioning
confidence: 64%
See 1 more Smart Citation